The Application of Computer Vision Technology in the Field of Agricultural Automation - Gao, Xue (Journal of Theory and Practice of Management Science, 2025)
With the rapid development of artificial intelligence and machine learning technology, computer vision has become an important driving force in the field of agricultural automation. This article explores the application of computer vision technology in agricultural automation, including crop pest and disease detection, harvesting robot navigation, crop growth monitoring, and automation control of agricultural machinery. The article analyzes the technical principles and practical effects of these applications, while pointing out the challenges and coping strategies in the implementation process. Finally, the article predicts the future development trend of computer vision in the field of agricultural automation, emphasizing its important role in promoting agricultural modernization and improving production efficiency.